PEMBELAJARAN BERBASIS PROYEK PADA MATA KULIAH PSIKOLOGI KEWIRAUSAHAAN DALAM MENINGKATKAN SIKAP ENTREPRENEUR MAHASISWA SEMESTER VII PRODI BK - Chr. Argo Widiharto; Wiwik Kusdaryani; Agus Setiawan (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2014)
The purpose of this research was knowing the effectiveness of project-based learning in a psychology enterpreneurship class. This quantitative research methods is using experimental pretest-posttest control group design. The population and sample that was used in this research were college students seventh semester of guidance counseling department in academic year 2014/2015 that was totaling 182 college students. The collecting data was used attitude scale enterpreneurship. The result in this research showed that difference between experimental group and control group in final evaluation showed a score of 14,36. The result were not much different also, it was demonstrated by t-test that was done which provide the result of thitung 16,201 while ttable 1,980 at significance level?é?á mistake at 0,05?é?á it can be said that thitung>ttable. It gave the illustration that project-based learning increases the enterpreneurship attitude of college students. Keywords: Project-based learning, entrepreneurship, college students seventh semester of guidance counseling department